The impact of human CES1 genetic variation on enzyme activity assessed by ritalinic acid/methylphenidate ratios. Issue 1 (24th April 2019) - Stage, Claus; Dalhoff, Kim; Rasmussen, Henrik Berg; Schow Guski, Louise; Thomsen, Ragnar; Bjerre, Ditte; Ferrero‐Miliani, Laura; Busk Madsen, Majbritt; Jürgens, Gesche
Abstract: The present clinical trial investigated the impact of selected SNPs in CES1 on the metabolic activity of the enzyme. For this purpose, we used methylphenidate (MPH) as a pharmacological probe and the d ‐RA/ d ‐MPH (metabolite/parent drug) ratios as a measure of enzymatic activity. This metabolic ratio (MR) was validated against the AUC ratios (AUC d ‐RA /AUC d ‐MPH ). CES1 SNPs from 120 volunteers were identified, and 12 SNPs fulfilling predefined inclusion criteria were analysed separately, comparing the effect of each genotype on the metabolic ratios. The SNP criteria were as follows: presence of Hardy‐Weinberg equilibrium, a minor allele frequency ≥ 0.01 and a clearly interpretable sequencing result in at least 30% of the individuals. Each participant ingested 10 mg of racemic methylphenidate, and blood samples were drawn prior to and 3 hours after drug administration. The SNP analysis confirmed the considerable impact of rs71647871 (G143E) in exon 4 on drug metabolism. In addition, three volunteers with markedly lower median MR, indicating decreased CES1 activity, harboured the same combination of three SNPs in intron 5. The median MR for these SNPs was 8.2 for the minor allele compared to 16.4 for the major alleles ( P = 0.04). Hence, one of these or the combination of these SNPs could be of clinical significance considering that the median MR of the G143E group was 5.4. The precise genetic relationship of this finding is currently unknown, as is the clinical significance.